Предмет: Алгебра,
автор: natalyamasson
(Х-2)(х+3)-9=х-6реши уравнение
Ответы
Автор ответа:
0
х²+3х-2х-6-9=х-6
х²+3х-2х-9=х
х²-9=0
х²=9
х=3
х=-3
х1=-3
х2=3
х²+3х-2х-9=х
х²-9=0
х²=9
х=3
х=-3
х1=-3
х2=3
Автор ответа:
0
(Х-2)(х+3)-9=х-6
x²+3x-2x-6-9=x-6
x²-9=0
(x-3)(x+3)=0
x=3
x=-3
x²+3x-2x-6-9=x-6
x²-9=0
(x-3)(x+3)=0
x=3
x=-3
Похожие вопросы
Предмет: Литература,
автор: wrl31iejdj
Предмет: Английский язык,
автор: bogdana2288
Предмет: Русский язык,
автор: balet123
Предмет: Математика,
автор: прнг7е
Предмет: Математика,
автор: aliskamuraveva